Informações de tecnologia de aplicação contidas nas bulas de agrotóxicos utilizados na cultura do sorgo no Brasil - Saint Paul, Agronome Paul (2023)
All stages of sorghum development, from seed to harvest, are susceptible to the attack of distinct groups of pests. Therefore, to ensure the maximum efficiency of an application, the correct adoption of the recommended application technology is necessary. In this case, the information and recommendations provided in the labels should ensure the responsible application of the product, as the use of pesticides is not without consequences for the environment and human health. The objective of this research was to study the information on application technology contained in the leaflets of pesticides registered for sorghum cultivation in Brazil, to promote discussion on the quality of the information provided and to verify whether it is sufficient to guide field application. The study was based on consultation with the Pesticides System Platform - AGROFIT of the Ministry of Agriculture, Livestock and Supply (MAPA). The information gathering and processing processes were conducted between April 15th and September 13th, 2021. From the collected data, control tables and graphs were prepared for the following: general information; information about application rate, syrup and water in the application of agrochemicals; season, phase, interval and number of applications of agrochemicals; information about the use of adjuvants; information about environmental protection and the applicator; information about the technical regulation parameters that can affect the application. Through this inventory, it was possible to verify that the information provided by the labels is insufficient to ensure proper application of the products. Manufacturers need to improve the content of the information to better guide the technician in the field.